The Effect of Metacognitive Strategy on Students' Reading Comprehension of Academic Text - Febriani, Hanura (Journal of Social Work and Science Education, 2022)
Reading comprehension is an active reading process in which students can dig up information in reading sources. These skills are very important so that students are able to adapt and compete in facing future challenges. In the reading process, students are required to be active and understand how and when to implement strategies so that reading comprehension is more effective. One strategy that can be used is the metacognitive strategy. Metacognitive abilities are very important for reading achievement. The Purpose of Metacognitive is to prepare further develop readers to become more aware of their thinking alone while reading. Educators provide express preparation on the use of reading strategies. Metacognitive strategy trains students to manage themselves to get reading comprehension. This research aims to investigated whether there was significance difference on students reading comprehension of academic text by using metacognitive strategy and who are not. The research used quasi experiment, all students of six semesters were the population of the research while techniques sampling was purposive sampling. Six semester students from 6A and 6D are the sample in this research. From data analysis and finding, metacognitive give positive effect toward students reading comprehension of academic texts. Sig. (2-tailed) value was 0.015 < 0.05 means that Ho was rejected and Ha was accepted. It conclude that there was significance difference on students’ reading comprehension of academic text score thought by metacognitive and conventional strategy.